Effect of Three Technical Arms Swings on The Elevation of the Center of Mass During a Standing Back Somersault - Mkaouer, Bessem (Akademia Wychowania Fizycznego w Katowicach, 2014)
Arms swing during standing back somersaults relates to three different “gymnastics schools”, each is considered “optimal” by its adepts. In the three cases, technical performance, elevation and safety differ. Therefore, the aim of this study was to compare the mechanical variables of three different arms swing techniques in the performance of a standing back tucked somersault. Five high-level male gymnasts (age: 23.17±1.61 yrs; body height: 1.65±0.05 m; body mass: 56.80±7.66 kg) randomly performed standing somersaults under three conditions, each following a different arms’ swing technical angle (270°, 180° and 90°). A force plate synchronized with a three dimensional movement analysis system was used to collect kinetic and kinematic data. Significant differences were observed between somersaults’ performance. The back somersault performed with 270° arms swing showed the best vertical displacement (up to 13.73%), while the back somersaults performed with 180° arms swing showed a decrease in power (up to 22.20%). The back somersault with 90° arms swing showed the highest force (up to 19.46%). Considering that the higher elevation of the centre of mass during the flight phase would allow best performance and lower the risk of falls, this study demonstrated that optimal arms’ swing technique prior to back tucked somersault was 270°.